2020
DOI: 10.1002/hpja.342
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and associated harms among university students in Australia: Findings from a cross‐sectional study

Abstract: Issue addressed University students regularly report alcohol consumption in excess of Australian guidelines for harm. However, previous studies have overlooked the experiences of mature‐aged students. This study assessed alcohol consumption and alcohol‐related harms among university students aged 18‐50 years old in Australia. Methods A cross‐sectional online survey with convenience sample of university students was used in this study. Unadjusted ordinal logistic regressions were performed to explore associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…While this study has noted strengths, it also has noted limitations. Response rates to surveys and interviews were lower than anticipated with only 21 graduates (8%) completing the questionnaire and 6 (2%) participating in the interviews; however, this is consistent with previous studies using university student samples that have shown similar low response rates (Bennett et al, 2006;Porter & Umbach, 2006;Tanudjaja et al, 2020). The sample was also relatively homogenous, being from one Australian public university.…”
Section: Discussionsupporting
confidence: 85%
“…While this study has noted strengths, it also has noted limitations. Response rates to surveys and interviews were lower than anticipated with only 21 graduates (8%) completing the questionnaire and 6 (2%) participating in the interviews; however, this is consistent with previous studies using university student samples that have shown similar low response rates (Bennett et al, 2006;Porter & Umbach, 2006;Tanudjaja et al, 2020). The sample was also relatively homogenous, being from one Australian public university.…”
Section: Discussionsupporting
confidence: 85%
“…The proportion of PSTs who consented to be involved in the study was 284/555 (51.1%), which was considered average in comparison to previous studies that have investigated university student response rates in the United States 23 and Australia. 24 , 25 , 26 Nine participants were excluded due to missing data. A final sample of n = 275 (age range = 18‐54; median age = 21 years; second years = 227 (82.5%); fourth years = 46 (16.7%) were included in the analyses (See Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, recent research among Australian university students reveals that 82% of students drank alcohol, and 50% of them exceeded the recommended limit. (Tanudjaja et al, 2021). In Australia, men and women are advised not to exceed ten standard drinks per week or four on a single occasion.…”
Section: Alcohol Use and Misuse In Tertiary Institutionsmentioning
confidence: 99%